2012
DOI: 10.3329/jom.v13i1.7980
|View full text |Cite
|
Sign up to set email alerts
|

Incorrect Inhaler Technique Compromising Quality of Life of Asthmatic Patients

Abstract: Abstract:Objective: The inhalation route is widely used for the treatment of asthma. It Results: There was an inverse relationship between education level and incorrect inhaler technique (p<0.05). Education of inhaler usage provided by doctors was more effective as compared to education provided by nurses (p<0.038). There was no significant relationship between age, sex, duration of asthma, duration of inhaler use, frequency of inhaler use and incorrect inhaler technique. Conclusion: Quality of life of a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 10 publications
6
40
2
2
Order By: Relevance
“…Age and gender are affective in both correct use and adherence to therapy. In accordance with our results, male or young patients are reported to use inhaler devices more correctly than female or older patients in previous studies conducted among adults [8,9]. One of the reasons of higher frequency of correct use and adherence to therapy in younger patients in our study may be that treatment is usually administered by parents for younger patients.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Age and gender are affective in both correct use and adherence to therapy. In accordance with our results, male or young patients are reported to use inhaler devices more correctly than female or older patients in previous studies conducted among adults [8,9]. One of the reasons of higher frequency of correct use and adherence to therapy in younger patients in our study may be that treatment is usually administered by parents for younger patients.…”
Section: Discussionsupporting
confidence: 94%
“…In studies conducted among adult asthmatics, 16.3-88% of patients were reported to use their inhaler devices with adequate performance [1,5,9,10]. The frequency of using MDI devices correctly was reported as 12-68% [1,10,23,24] and frequency of using DPI devices correctly was reported as 21.8-88% [1,25,26].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is worth to mention that inhaler use technique is considered as dealing with a simple device, so it is often neglected in the general medical textbooks and literature (11) . A review of medical textbooks used in the education of physicians revealed that only two out of 40 books included a simple list of steps for proper pressurized metered-dose inhaler (pMDI) use (12) . As a result, 39-67% of nurses, doctors, and respiratory therapists were reported to be unable to adequately describe or perform critical steps for using inhalers (4) .…”
Section: Technical Errors In Using Inhalers Among Patients With Asthmmentioning
confidence: 99%